Conservation challenges for Brazilian primates and the role of protected areas in a changing climate - Braga Gomes, Letícia (2024)
The negative effects of land-use changes on biodiversity significantly contribute to climate change. Primates are among the animals most affected by these changes, because of their high dependence on forest cover where a lack of forest connectivity can limit their dispersal and segregate their populations. In this sense, protected areas (PAs) are crucial for conserving endangered primates, especially endemic species. Using species distribution models, we assessed the impact of climate change and deforestation on the geographic distribution of 35 endangered Brazilian primates. We also evaluated the potential of PAs to retain suitable habitats for primate species under current conditions (baseline) and four future climate scenarios (optimistic and pessimistic, both for the periods 2041–2060 and 2061–2080), as well as the capacity of PAs to preserve species’ geographic representation both now and in the future. Our findings indicate that most primate taxa would experience a significant loss of suitable area (> 90%) in both pessimistic and optimistic scenarios. For future scenarios, the loss could exceed 98% for 10 taxa, particularly Amazonian species. Regarding PAs potential to retain suitable areas for maintaining the richness of threatened primates, only 8.6% harbor more species than expected by chance (1–6 taxa) in the baseline conditions, with a decrease in future scenarios. Results suggest that taxa already threatened with extinction are inadequately protected by PAs in the baseline conditions and even less so in future scenarios. Given the restricted geographic distribution and current population decline for most taxa, we emphasize the need to increase the number of PAs to ensure population viability and prevent future extinction.